The Consistency between the Concluding Verses of the Surahs and the Opening Verses of their Following Surahs of the Quran: Analytical Study - Imar, Mihamad Ibrahim Mosa; Balhaj, Faraj (Journal of Islamic Sciences, 2022)
The study aims at identifying the relation between the concluding verses of the surahs and the opening verses of the following surahs of the Quran to clarify and show the connection and consistency between the verses of the Quran and explain the miraculous part of it. The researcher used the deductive approach by mentioning examples from some of the concluding verses of the surahs and the opening verses of their following surahs. The study has found that there is a relation between the concluding verses of the surahs and the opening verses of their following surahs. It is an integrative relation that originated a consistent and integral Qur’anic construction between the verses and the rulings of the verses through the examples that were explained with the help of Tafsir. The study recommended conducting more research about this subject for its importance in dismissing the suspicions of lacking connections and consistency between the surahs of the Quran.